Validity of Ethnoscience Based Chemistry Learning Media Emphasizing Character Values and Conservation Behavior - Rizki Utari; Yayuk Andayani; Lalu Rudyat Telly Savalas; Yunita Arian Sani Anwar (Postgraduate, University of Mataram, 2021)
This study aims to obtain a valid chemistry learning device based on ethnoscience emphasizing character values and conservation behaviors. This study refers to the 4D model from Tiahgrajan, S. Semmel & Semmel which was modified into three stages, namely define, design, and develop. The chemistry learning kit that has been validated by three experts consisted of ethnics-based chemistry modules, lesson plans, student worksheets, and questionnaire sheets. The validity of chemistry learning devices was analyzed using the Aiken's V formula which was consulted to the criteria in the validity table. The results showed that the developed devices were appropriate for use in learning with an individual score of each component as follows: the implementation plan of learning got a score of 0.91 (very valid), the Chemistry module got a score of 0.91 (very valid), the student worksheet got a score of 0.89 (very valid), and the poll got a score of 0.72 (valid)